Stigma as a Social Determinant of Health: A Policy Classification Framework and Call to Action - LISA CARTER‐BAWA (The Milbank Quarterly, 2026)
Policy Points Stigma functions as a social determinant of health (SDOH), producing population health inequities through resource deprivation, social exclusion, constrained health care, physiological stress, and diminished agency—yet it lacks formal SDOH classification. Because stigma operates as a fundamental cause of health inequalities, policy responses must extend beyond health care systems to encompass housing, employment, education, and social participation. Discrimination is already classified as an SDOH; formal stigma classification would address the broader ecosystem that enables discrimination and the anticipated, internalized, and structural forms that produce harm even in its absence. Context Despite substantial evidence that stigma produces measurable health inequities across conditions and populations, stigma remains absent from major social determinants of health (SDOH) frameworks. This absence persists even though discrimination—one manifestation of the broader stigma ecosystem—is already classified as an SDOH. Methods Drawing on fundamental cause theory, we derive five criteria for SDOH classification and systematically evaluate stigma against each. We synthesize evidence from systematic reviews and meta‐analyses across HIV, mental illness, lung cancer, obesity, and structural stigma research. Lung cancer serves as a running exemplar throughout. Findings Stigma meets all five criteria for SDOH classification: structural embedding in policies and institutions, health impact through multiple pathways extending well beyond health care systems, contribution to systematic health inequities, modifiability through multilevel intervention, and measurement feasibility through validated instruments. We identify five pathways through which stigma produces population health harm: resource deprivation, social exclusion, constrained health care access and quality, physiological stress and weathering, and diminished agency and identity. Conclusions We propose the stigma‐as‐social‐determinant (SSD) classification framework as a policy translation tool that specifies the infrastructure needed to operationalize formal recognition. Critically, because stigma operates as a fundamental cause whose health effects extend far beyond clinical encounters, policy translation must not flow primarily through health care systems. Anti‐stigma policy must engage housing, employment, education, and social policy alongside—not subordinate to—health care reform.